Peran Guru Kristen sebagai Penuntun dalam Mewujudkan Pendidikan Karakter yang Holistis-Transformasional - Pardede, Ayu Agustina; Listiani, Tanti (Harati: Jurnal Pendidikan Kristen, 2024)
The decline in character is the fruit of the ineffective implementation of transformational-holistic character education. Christian teachers are important in understanding their duties and functions as guides to revitalize character education that touches aspects of students' lives as a whole: cognitive, affective, and psychomotor. Therefore, the purpose of writing this paper is to describe the role of the Christian teacher as a guide in realizing holistic transformational character education. The writing method used is the method of literature review. Holistic-transformational character education is important because students can find identity, meaning, and purpose in life through interaction with the environment and God. Christian teachers must always establish relationships with students, and have a personal relationship with God so that they can imitate Christ as the Great Shepherd, center Christ in education, and have an eschatological mission. This can be realized through strategies, methods, and teaching models that are varied and by the needs of students; providing motivation and support; and presenting good, rich material that remains grounded in Bible truth. Future researchers should examine the social competence of Christian teachers with homeroom/BK, parents, and students in realizing the above.